2005
DOI: 10.1021/la047302p
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Dynamic Adsorption/Desorption on Zeolite 5A Studied by 13C Magnetic Resonance Imaging

Abstract: We present the first 13C magnetic resonance imaging study of CO2 transient adsorption/desorption processes in a zeolite 5A column. CO2 transient concentration profiles were measured with a centric scan spin-echo single point imaging technique. The adsorption wave profiles were determined under flow conditions, with the results analyzed by the Bohart-Adams model. The model adequately accounts for the spatial and the temporal behavior of CO2 in the column. CO2 adsorption rate constants were calculated from the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 23 publications
(25 reference statements)
1
39
0
Order By: Relevance
“…Several technologies to separate and capture the industrial emissions of CO 2 have been developed. Among them, certain technologies are based on the CO 2 adsorption/desorption by using natural and synthetic zeolites [3,4]. The zeolites are a subclass of tectosilicates that possess a framework formed by a threedimensional assemblage of tetrahedra [SiO 4 ] and [(AlO 4 )-].…”
Section: Introductionmentioning
confidence: 99%
“…Several technologies to separate and capture the industrial emissions of CO 2 have been developed. Among them, certain technologies are based on the CO 2 adsorption/desorption by using natural and synthetic zeolites [3,4]. The zeolites are a subclass of tectosilicates that possess a framework formed by a threedimensional assemblage of tetrahedra [SiO 4 ] and [(AlO 4 )-].…”
Section: Introductionmentioning
confidence: 99%
“…Zeolites functionalized with molecular targeting vectors (e.g., peptides, aptamers) that enable specific high-affinity binding to in vivo molecular targets (such as cell surface receptors) were investigated. In addition, these materials possess unique properties that enable radionuclides and contrast agent metals to be concentrated for applications in magnetic resonance imaging (MRI) and positron emission tomography (PET) [63][64][65][66][67].…”
Section: Zeolite For Antimicrobial and Medical Applicationsmentioning
confidence: 99%
“…Gladden et al (2002) demonstrated that by monitoring the 1 H chemical shift, spatial variation in liquid phase esterification of methanol and acetic acid in fixed bed reactors under flow conditions could be visualized. A limited number of studies have applied MRI to investigate reactive transport in porous media, including CO 2 adsoption/desorption on zeolites (Cheng et al, 2005), and metal ion sorption on glass beads (Moradi, 2008) and quartz sands (Nestle et al, 2003). Cheng et al (2005) applied 13 C MRI (2.35T magnet, 100 Gauss/cm) to investigate the adsorption / desorption kinetics of pure gas and condensed phase CO 2 on 8 – 12 mesh zeolite 5A beads, and a centric scan spin-echo single point imaging technique was employed to obtain transient 1D CO 2 density profiles with a 1 mm resolution.…”
Section: Imaging Applicationsmentioning
confidence: 99%